Clinical psychology referral for individuals with auditory verbal hallucinations and schizophrenia: Therapy engagement, hallucination severity and distress. (August 2022) - Solar, Ann; Bennett, Kellie; Hulse, Gary
Objective: Test an intervention for people with schizophrenia and auditory verbal hallucinations at an acute inpatient unit (AIU) to engage with community therapy and reduce hallucination severity and associated distress. The trial cohort consisted of patients who after assessment by an AIU psychiatrist were not selected for an appointment with an AIU clinical psychologist and an opportunity for referral to a post-discharge community psychologist. An intervention providing the appointment and referral opportunity was compared to Treatment As Usual (TAU). Method: A single-blind, randomised, control trial compared the intervention with TAU over 6-months post-discharge using Engagement in Community Therapy, Psychotic Symptom Rating Scale (PSYRATS) auditory hallucinations and Revised Beliefs About Voices (BAVQ-R) questionnaires. Results: Post-discharge community therapy engagement increased at 6 months compared to baseline in the intervention, TAU and combined groups. PSYRATS AHS and H-DIS scores decreased from baseline to last follow-up (statistically significant for TAU, and combined treatment groups). BAVQ-R RE scores decreased from baseline to last follow-up but the decrease was not statistically significant. Conclusions: Most participants chose to engage with a community therapist despite not being initially assigned for referral by their psychiatrist and experiencing moderately severe symptoms.